Contemporary Da’wah: Bullying in Schools as a Da’wahProblem: Dakwah Kontemporer: Bullying di Sekolah sebagai Masalah Dakwah - Prasongko, Wahyu Agung; Hamidah, Lilik (Transformatif, 2024)
Bullying can cause adverse physical and mental effects on victims, including stress, depression, and social isolation. Bullying contradicts the values of Islamic teachings, which emphasize compassion, justice, and respect for others. In the context of da'wah (Islamic preaching), it is important for preachers (da'i) to understand and address the issue of bullying in accordance with religious teachings. The purpose of this research is to discuss the bullying issues occurring in society and provide recommendations and solutions for da'i in addressing or delivering da'wah related to bullying cases. This study is descriptive-qualitative research using a literature review approach. The primary data sources include the Qur'an, hadith, and relevant documents. Secondary data are derived from scientific studies, articles, journals, and books discussing the phenomenon of bullying. Data analysis is conducted by deeply interpreting the collected data and then concluding. The research results identified several factors contributing to bullying in schools, including individual factors, such as a sense of superiority (having power), lack of supervision by teachers or educators, family or parental influences, and peer factors. Preventive steps for da'i to address bullying are by giving an understanding of retaliating with no harm action, building friendships, supporting networks, relocating to a better environment (hijrah), self-defense, education, and awareness. As da'i, they can share stories of the Prophet and his companions that illustrate good behavior, instill empathy and tolerance, and encourage positive behavior to prevent bullying.